Mobile Genetic Elements Drive Antimicrobial Resistance Gene Spread in Pasteurellaceae Species - da Silva, Giarlã Cunha; Gonçalves, Osiel Silva; Rosa, Jéssica Nogueira; França, Kiara Campos; Bossé, Janine Thérèse; Santana, Mateus Ferreira; Langford, Paul Richard; Bazzolli, Denise Mara Soares (Frontiers in Microbiology, 2022)
Mobile genetic elements (MGEs) and antimicrobial resistance (AMR) drive important ecological 19 relationships in microbial communities and pathogen-host interaction. In this study, we investigated 20 the resistome-associated mobilome in 345 publicly available Pasteurellaceae genomes, a large 21 family of Gram-negative bacteria including major human and animal pathogens. We generate a 22 comprehensive dataset of the mobilome integrated into genomes, including 10,820 insertion 23 sequences, 2,939 prophages, and 43 integrative and conjugative elements. Also, we assessed plasmid 24 sequences of Pasteurellaceae. Our findings greatly expand the diversity of MGEs for the family, 25 including a description of novel elements. We discovered that MGEs are comparable and dispersed 26 across species and that they also co-occur in genomes, contributing to the family's ecology via gene 27 transfer. In addition, we investigated the impact of these elements in the dissemination and shaping 28 of AMR genes. A total of 55 different AMR genes were mapped to 721 locations in the dataset. 29 MGEs are linked with 77.6% of AMR genes discovered, indicating their important involvement in 30 the acquisition and transmission of such genes. This study provides an uncharted view of the 31 Pasteurellaceae by demonstrating the global distribution of resistance genes linked with MGEs.